Combination Treatment with Thread-Embedding Acupuncture and Electroacupuncture for Knee Osteoarthritis Patients with Postoperative Pain: A Randomized Controlled Feasibility Study - Lee YJ; Han CH; Jeon JH; Kim E; Park KH; Kim AR; Kim YI (Journal of Pain Research)
Ye Ji Lee,1,* Chang-Hyun Han,2,3,* Ju Hyun Jeon,1 Eunseok Kim,4,5 Ki Hyun Park,6 Ae Ran Kim,7 Young Il Kim1 1Department of Acupuncture and Moxibustion Medicine, College of Korean Medicine, Daejeon University, Daejeon, Republic of Korea; 2KM Science Research Division, Korea Institute of Oriental Medicine, Daejeon, Republic of Korea; 3Korean Convergence Medicine, University of Science and Technology (UST), Campus of Korea Institute of Oriental Medicine, Daejeon, Republic of Korea; 4Department of Acupuncture and Moxibustion Medicine, Pusan National University Korean Medicine Hospital, Yangsan, Republic of Korea; 5Division of Clinical Medicine, School of Korean Medicine, Pusan National University, Yangsan, Republic of Korea; 6KM Data Division, Korea Institute of Oriental Medicine, Daejeon, Republic of Korea; 7Clinical Research Coordinating Team, Korea Institute of Oriental Medicine, Daejeon, Republic of Korea*These authors contributed equally to this workCorrespondence: Young Il Kim, Department of Acupuncture and Moxibustion Medicine, College of Korean Medicine, Daejeon University, Daejeon, Republic of Korea, Email omdkim01@dju.krPurpose: This study aimed to evaluate the effectiveness and safety of combination treatment with thread-embedding acupuncture (TEA) and electroacupuncture (EA) in patients with persistent knee pain after arthroscopic surgery, autologous chondrocyte implantation, or autologous osteochondral transplantation.Patients and Methods: Twelve patients with knee osteoarthritis (KOA) who experienced postoperative pain were randomized to either the treatment group (TG) or control group (CG) in a 1:1 ratio. The TG received TEA once a week for four sessions and EA twice a week for eight sessions while continuing usual care, defined as standard conventional treatments. The CG received only usual care for four weeks. The primary outcome was the visual analogue scale (VAS) score at week 4 compared with the baseline. The secondary outcomes were the VAS scores at weeks 2, 6, and 8, the Korean version of the Western Ontario and McMaster Universities Osteoarthritis Index (K-WOMAC), the EuroQol 5-Dimension 5-Level (EQ-5D-5L), and rescue medication consumption at weeks 2, 4, 6, and 8. Adverse events were assessed at each visit.Results: The TG showed significant improvement in the VAS scores at weeks 4, 6, and 8 compared with the CG (week 4: − 24.5; p = 0.0106, week 6: − 19.667; p = 0.0228, week 8: − 28.667; p = 0.0036). In the TG, significant differences were observed in K-WOMAC total scores at weeks 2, 4, 6, and 8 (week 2: 17.167; p = 0.0083, week 4: 23; p = 0.0018, week 6: 29.833; p = 0.0009, week 8: 30.5; p = 0.0006); however, there were no differences between the two groups. The two groups had no significant differences in the EQ-5D-5L and rescue medication consumption. No adverse events were observed in either groups during the study period.Conclusion: This feasibility study suggests that adding combination treatment with TEA and EA to usual care might relieve pain in patients with KOA. Large-scale clinical trials are needed to confirm the long-term effects of combination treatment.Keywords: thread-embedding acupuncture, electroacupuncture, osteoarthritis, knee, randomized controlled trial